HR CHALLENGES IN THE ERA OF REMOTE LEADERSHIP: BUILDING A STRONG VIRTUAL TEAM - Raden Rudi Alhempi; Supaphorn Akkapin; Raja Marwan Indra Saputra; Alief Feisal Haznil; Erfa Okta Lussianda (Jurnal Apresiasi Ekonomi, 2026)
This study aims to analyze the influence of remote leadership practices and HR policies and practices on team effectiveness through communication effectiveness in a virtual work environment at PT ABC in Riau. Changes in work patterns toward remote working systems require organizations to maintain coordination, collaboration, and team productivity continuously despite the limitations of direct interaction. This study employed a quantitative approach using a nonprobability sampling technique involving 90 employees of PT ABC in Riau. The research data were analyzed using Structural Equation Modeling (SEM) based on SmartPLS to examine both direct and indirect relationships among variables. The results indicate that remote leadership practices and HR policies and practices have a positive and significant effect on communication effectiveness and team effectiveness. Furthermore, communication effectiveness was proven to strengthen the relationship between remote leadership and HR policies on team effectiveness in the context of virtual work. These findings suggest that effective communication is an essential element in aligning leadership strategies and HR management to create more adaptive and productive team collaboration. This study implies that organizations need to strengthen digital communication strategies, enhance virtual leadership competencies, and develop HR policies that support team work effectiveness in the era of digital transformation